Kids Mean Business - Marketers Beware! A Market Survey on Impact of Advertising on Kids - Vernekar, Sachin S.; Wadhwa, Preety (Indian Journal of Marketing, 2008)
Indian economy is continuously growing with the favourable demographics, income. This growth is reflected in the growing GDP, growth in PCI and the consequent rise in the Disposable income of an average Indian. The increase in disposable income and a psychological and economic transformation are acting like boosters for the Indian market. Indian market is now no more an Indigenous market rather it has made its presence globally felt. Not any particular sector but al sectors from manufacturing to retailing and all the industries from FMCG Consumer Durables Retail and IT products have shown a considerable growth.The largest kid market in the world, India, is changing rapidly in favor of the child not only as an influencer but also as a decision maker. Children in middle-class India take important decisions in the home, thereby contributing majorly to household budget contours. From buying white goods and cars, to cell phones and grocery and even insurance policies, children under the age of 13 are deciding which brands their parents should or should not buy. The kids market remains crucially important as the marketers seek to attract a new audience and build brand loyalty at a very young age. The paper plans to study the "impact of increase in disposable income on the spending pattern of parents across categories and how kids influence their parents in buying decisions. The effect of TV Advertisements on School Going Children has also been studied.